When Debunking Scientific Myths Fails (and When It Does Not): The Backfire Effect in the Context of Journalistic Coverage and Immediate Judgments as Prevention Strategy. (February 2016) - Peter, Christina; Koch, Thomas
When reporting scientific information, journalists often present common myths that are refuted with scientific facts. However, correcting misinformation this way is often not only ineffective but can increase the likelihood that people misremember it as true. We test this backfire effect in the context of journalistic coverage and examine how to counteract it. In a web-based experiment, we find evidence for a systematic backfire effect that occurs after a few minutes and strengthens after five days. Results show that forming judgments immediately during reception (in contrast to memory-based) can reduce backfire effects and prevent erroneous memory from affecting participants' attitudes.